2015
DOI: 10.1021/jf506239b
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Magnetic Molecularly Imprinted Polymers as Sorbent for Sulfonylurea Herbicide Residues

Abstract: Sulfonylurea herbicides are widely used at lower dosage for controlling broad-leaf weeds and some grasses in cereals and economic crops. It is important to develop a highly efficient and selective pretreatment method for analyzing sulfonylurea herbicide residues in environments and samples from agricultural products based on magnetic molecularly imprinted polymers (MIPs). The MIPs were prepared by a surface molecular imprinting technique especially using the vinyl-modified Fe3O4@SiO2 nanoparticle as the suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…It was observed that the vibration peak at 1630 cm −1 corresponding to the stretching vibration of C=C in MPS further proved that SiO 2 @Fe 3 O 4 was successfully grafted with MPS. Those results are consistent with that of other researches [40,41].…”
Section: Ftir Spectroscopysupporting
confidence: 94%
See 1 more Smart Citation
“…It was observed that the vibration peak at 1630 cm −1 corresponding to the stretching vibration of C=C in MPS further proved that SiO 2 @Fe 3 O 4 was successfully grafted with MPS. Those results are consistent with that of other researches [40,41].…”
Section: Ftir Spectroscopysupporting
confidence: 94%
“…The adsorption capacity of the MMIPs for AO is the highest, which means that template molecule has a higher selective affinity to the MMIPs than its analogues [25]. It may be related to the size and functional groups of recognition sites, and the interaction is mainly due to hydrogen bond and ionic interaction [39,40]. Low adsorption capacity of MMIPs for chrysoidine was observed due to the different structure in comparison with AO and AOHCl, and the adsorption capacity of MNIPs for AO is almost the same with AOHCl, but much higher than chrysoidine due to the structural difference.…”
Section: Rebinding and Enrichment Experimentsmentioning
confidence: 99%
“…Among them, there can be found pyrethroids [46,60], carbamates [61], organochlorine pesticides (OCPs) [62,63] or OPPs [45, 64,65], phenylurea [53] and sulfonylurea herbicides [66] although nanomaterials have also been suitability applied for pesticide multiresidues extraction [48,49,51].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…MIPs are workable to maximize the selectivity and sensitivity of detection sensors as recognition elements [4]. MIPs are widely used in the environmental [12], agricultural [13], food science [14], and pharmaceutical industries [15]. With the development of science and technology and the appearance of advanced instruments, the relatively homogeneous MIPs could not satisfy the growing technological requirements [16].…”
Section: Introductionmentioning
confidence: 99%